Examining neighbourhood-level disparities in Black, Latina/o, Asian, and White physical health, mental health, chronic conditions, and social disadvantage in California - Qiuxi Li; Jason A. Douglas; Andrew M. Subica (Taylor & Francis Group, 2023)
ABSTRACTRacial/ethnic minority individuals in the U.S. experience numerous health disparities versus Whites, often due to differences in social determinants. Yet, limited large-scale research has examined these differences at the neighbourhood level. We merged 2021 PLACES Project and 2020 American Community Survey data across 3,211 census tracts (neighbourhoods) defined as majority (>50%) Black, Latina/o, Asian or White. T-tests and hierarchical linear regressions were used to examine differences and associations between neighbourhoods on key health (general health, mental health, obesity, diabetes, cancer, coronary heart disease, chronic obstructive pulmonary disease, stroke), and social outcomes (income, unemployment, age, population density). Results indicated that minority neighbourhoods in California exhibited stark health and social disparities versus White neighbourhoods, displaying worse outcomes on nearly every social and health variable/condition examined; particularly for Black and Latina/o neighbourhoods. Moreover, regression findings revealed that, after considering income, unemployment, and population density, (1) fair/poor mental health and higher percentages of Black, Latina/o and Asian residents in neighbourhoods independently associated with greater neighbourhood fair/poor physical health, and (2) fair/poor mental health significantly associated with greater prevalence of obesity and COPD. This study thus underscores the need to address the profound health and social disparities experienced by minority neighbourhoods for more equitable neighbourhoods.